2017
DOI: 10.1007/s10532-017-9814-9
|View full text |Cite
|
Sign up to set email alerts
|

Whole community transcriptome of a sequencing batch reactor transforming 2,4-dinitroanisole (DNAN) and 3-nitro-1,2,4-triazol-5-one (NTO)

Abstract: Two sequencing batch reactors (SBRs) were run to bio-mineralize 2,4-dinitroanisole (DNAN) and 3-nitro-1,2,4-triazol-5-one (NTO) in lab scale settings. The reactors were shown to reproducibly biotransform these munitions under aerobic and anaerobic conditions during the operations of these SBRs. Complete removal (100% biotransformation) of DNAN (initially 17.7 ± 5.4 mg L) and NTO (initially 15.0 ± 7.1 mg L) was observed in an anaerobic SBR when Luria-Bertani (LB) broth was present. In contrast, an aerobic SBR d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Bioreactors have been used to successfully degrade DNAN and NTO in synthetic wastewater with aerobic removal efficiencies of 58 ± 22% and 45 ± 24%, respectively when using purely aerobic methods ( Weidhaas et al., 2018 ). In addition, specific strains of microbial organism have been identified that are able to degrade DNAN completely despite the presence of other IHE ( Karthikeyan and Spain, 2016 ).…”
Section: Ihe Wastewater Treatment Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bioreactors have been used to successfully degrade DNAN and NTO in synthetic wastewater with aerobic removal efficiencies of 58 ± 22% and 45 ± 24%, respectively when using purely aerobic methods ( Weidhaas et al., 2018 ). In addition, specific strains of microbial organism have been identified that are able to degrade DNAN completely despite the presence of other IHE ( Karthikeyan and Spain, 2016 ).…”
Section: Ihe Wastewater Treatment Methodsmentioning
confidence: 99%
“…There have also been reports of DNAN, NTO and nitroguanadine (NQ) being degraded from mixed solution ( Richard and Weidhaas, 2014 ). Biodegradation systems that use multiple, sequenced reactors have shown more promise in removing IHE from wastewater with removal rates of up to 100% when using aerobic/anaerobic sequences ( Weidhaas et al., 2018 ). Alternative methods for increasing the removal efficiency of IHE from wastewater include the use of electron donors such as sodium pyruvate which was shown to increase the removal rate of NTO from solution in waster to 93.5% in an anaerobic-aerobic system ( Madeira et al., 2017 ).…”
Section: Ihe Wastewater Treatment Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Toward the identification of microbial genes responsible for DNAN detoxification, transcriptome analysis on microbial populations fed DNAN and NTO reported the upregulation of nitroreductase, hydroxylaminophenol mutase, 4-hydroxylphenyl acetate-associated genes, and quinone oxidoreductases (Weidhaas et al 2018).…”
Section: Dnan-detoxifying Microbial Systemsmentioning
confidence: 99%
“…To profile the communities involved in NTO biodegradation, a metagenomic approach used enrichment cultures supplemented with molasses, methanol, or thiosulfate and identified predominately Pseudomonadaceae, Clostridiaceae and Sporolactobacillaceae (Eberly et al 2016). The subsequent, whole community, transcriptome profiling on batch reactors dosed with NTO and DNAN revealed the upregulation of many genes implicated in the classic detoxification of xenobiotics (Weidhaas et al 2018). Among these was N-ethylmaleimide reductase, a member of the OYE family; other OYE homologs are able to transform nitrate ester and nitroaromatic explosives (Williams et al 2004).…”
Section: Nto-degrading Microbial Systemsmentioning
confidence: 99%